IT Governance Information System Audit Analysis using COBIT 4.1 Framework by measuring Maturity Level - Nurfadhiilah, Annisa; Faharuddin, Fadhli; Jumaryadi, Yuwan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Appropriate Information Technology governance is needed to measure Information Technology involvement. The Information Technology governance used in analyzing audits is the COBIT 4.1 framework, so that analyzing audits can be carried out in accordance with the standard provisions that have been established in this work framework. This research utilizes qualitative methods in the data collection process at PT. Expressindo System Network. Based on the results of the research conducted, it is known that the DS domain as a whole is at level 3, this means that the company is at the stage where it can carry out the procedures that have been determined. Apart from the DS domain, domains PO02, PO03, PO04, PO05, PO06, PO07, PO08, AI01, AI02, AI04, AI05, AI06, AI07, and ME01 are at maturity level 3. However, domains PO10, AI03, ME04 are at level 2 of the maturity level, where the company still needs to carry out training and development. The results of this research will determine the maturity level of the company and provide an evaluation in accordance with the COBIT 4.1 framework standards.